Effects of oral administration of S-1 on the pharmacokinetics of SN-38, irinotecan active metabolite, in patients with advanced colorectal cancer - Yokoo, Koji; Hamada, Akinobu; Tazoe, Kensuke; Sasaki, Yutaka; Saito, Hideyuki (Therapeutic drug monitoring, 2009)
Previous studies have assessed the efficacy and safety of combined treatment with irinotecan (7-ethyl-10-[4-[1-piperidino]-1-piperidino]carbonyloxycamptothecin, CPT-11) and S-1, containing tegafur, a prodrug of 5-fluorouracil, in the treatment of colorectal and gastric cancer. The objective of this study was to describe the interaction between CPT-11 and S-1 in 4 patients with colorectal cancer. Coadministration of S-1 changed the pharmacokinetic behavior of CPT-11 and its metabolites. In particular, maximum plasma concentration (Cmax) and area under the plasma concentration curve (AUC) of 7-ethyl-10-hydroxycampothecin (SN-38) was markedly decreased by coadministration of S-1. For SN-38, the median ratio of Cmax and AUC with S-1 to those without S-1 was median 0.34 (range 0.24-0.78) and 0.56 (range 0.23-0.68), respectively. A markedly difference in drug interaction among individual patients was observed. We conclude that the plasma concentration of SN-38 was decreased by oral administration of S-1 in patients with colorectal cancer. This observation might be important for clinical decisions regarding combination therapy.